Private Equity Waves - Han Smit; Ward A. van den Berg (Tinbergen Institute, 2006)
This study presents a dynamic model for the private equity market in which information revelation and uncertainty rationally explain the cyclical pattern of investment flows into private equity. The net benefit of private equity over public equity is i) uncertain and ii) agents have private information about the benefits of their investment. When these distinguishing characteristics determine investment behavior in private equity markets, rational investment waves may arise endogenously. Investment behavior reveals private information on the benefits of private equity financing and may trigger a cascade when investors jump on the bandwagon and invest irrespective of their private information content. We argue that the procyclical behavior of private equity volumes is strengthened by the revelation of information on the benefits of private equity investments. The occurrence and length of such waves in the market for private equity depend on the capabilities of agents.
Keywords: G24; G34; 330; private equity; information economics; Private Equity; Investitionsentscheidung; Informationsökonomik; Theorie